2020
DOI: 10.1007/s10549-020-05565-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the axilla in breast cancer: outcome analysis in a series of ductal versus lobular invasive cancers

Abstract: Introduction Axillary lymph node dissection (ALND) has been considered essential for the staging of breast cancer (BC). As the impact of tumor biology on clinical outcomes is recognized, a surgical de-escalation approach is being implemented. We performed a retrospective study focused on surgical management of the axilla in invasive lobular carcinoma (ILC) versus invasive ductal carcinoma (IDC). Materials and methods 1151 newly diagnosed BCs, IDCs (79.6%) or ILCs (20.4%), were selected among patients treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…110 Several studies report a higher nodal stage at diagnosis and a higher number of positive lymph nodes at the time of surgery in ILC compared to NST, resulting in a higher rate of axillary lymph node dissection. 9,10,111 This might be attributable to the larger tumour sizes and other confounding factors, as this was no longer seen in multivariate analysis. 112 Following sentinel lymph node biopsy, there is a 38% rate of nodal positivity in clinically node-negative patients, highlighting the challenges of clinical nodal assessment in ILC.…”
Section: Surgerymentioning
confidence: 96%
See 2 more Smart Citations
“…110 Several studies report a higher nodal stage at diagnosis and a higher number of positive lymph nodes at the time of surgery in ILC compared to NST, resulting in a higher rate of axillary lymph node dissection. 9,10,111 This might be attributable to the larger tumour sizes and other confounding factors, as this was no longer seen in multivariate analysis. 112 Following sentinel lymph node biopsy, there is a 38% rate of nodal positivity in clinically node-negative patients, highlighting the challenges of clinical nodal assessment in ILC.…”
Section: Surgerymentioning
confidence: 96%
“…In general, at diagnosis, women with ILC are slightly older than women with NST (mean age 63.4 versus 59.5 years, respectively). 8,9 ILC is more difficult to detect through standard screening programs and presents more often as a larger tumour 9 and with nodal involvement, 10 as compared to NST. Additionally, ILC is more often multifocal.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The axillary lymph node (ALN) involvement represents one of the most important prognostic factors in early BC [19][20][21][22][23][24][25]; however, previous studies have shown controversial results regarding the ALN status between ILC and IDC. There are many studies demonstrating that the ALN involvement does not differ between both groups [10,26,27]; however, some studies showed an association between ILC and a higher incidence of positive ALN involvement [8,28,29]. In contrast, there are studies reporting less frequent ALN positivity in ILC [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding the implementation of SLNB in patients with invasive lobular carcinoma (ILC) is sparse. Whether ILC patients with 1-2 positive SLNs can be exempted from ALND remains controversial (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%